Symptoms of titanium and nickel allergic sensitization in orthodontic treatment - Martina Zigante; Marijana Rincic Mlinaric; Marija Kastelan; Vjera Perkovic; Magda Trinajstic Zrinski; Stjepan Spalj (SpringerOpen, 2020)
Abstract Aim The study aimed to evaluate to which extent self-reported symptomatology, age, and sex are predictors of titanium and nickel allergic sensitization in patients in treatment with fixed orthodontic appliances. Methods The study analyzed 228 subjects aged 11-45 years (median 18, interquartile range 16-22); 68% of them were females, and 52% were adolescents. The allergic sensitization testing included epicutaneous patch test to titanium, titanium dioxide, titanium oxalate, titanium nitride, and nickel sulfate. The questionnaire on symptoms potentially linked to titanium and nickel sensitization was used. Results Prevalence of the allergic sensitization to titanium in patients undergoing orthodontic treatment was 4% (2% only to titanium without nickel) while to nickel 14% (12% nickel without titanium). Hypersensitivity to both metals at the same time was present in 2% of subjects. Sensitization to nickel was more common in females than in males (17 vs. 8%) and much more common in adults than in adolescents with small effect size (20 vs. 8%; p = 0.013). Sensitization to titanium was more common in females than in males (6 vs. 1%) with no difference in age. Multiple logistic regression analysis revealed that adult age increases the odds for being sensitized to nickel for 2.4 × (95% CI 1.1-5.6; p = 0.044) while watery eyes for 3.7 × (95% CI 1.2-11.1; p = 0.022). None of the symptoms were significant predictors of titanium sensitization. Conclusion Allergic sensitization to titanium and nickel are not very frequent in orthodontic patients, and self-reported symptomatology is a weak predictor of those sensitizations.